At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine which equation is equivalent to the given equation [tex]\( 2x - 4(2x - 8) = 5x \)[/tex], follow these steps:
1. Start with the original equation:
[tex]\[ 2x - 4(2x - 8) = 5x \][/tex]
2. Simplify the left-hand side by distributing the [tex]\(-4\)[/tex] across the terms within the parentheses:
[tex]\[ 2x - 4(2x - 8) = 2x - 4 \cdot 2x + 4 \cdot 8 \][/tex]
Simplify the multiplication inside:
[tex]\[ 2x - 8x + 32 \][/tex]
3. Combine like terms on the left-hand side:
[tex]\[ 2x - 8x + 32 = -6x + 32 \][/tex]
4. Rewrite the simplified equation:
[tex]\[ -6x + 32 = 5x \][/tex]
At this point, the simplified version of the given equation is [tex]\(-6x + 32 = 5x\)[/tex].
Let's match this to the provided options:
1. [tex]\( -6x - 8 = 5x \)[/tex]
2. [tex]\( -4x + 32 = 5x \)[/tex]
3. [tex]\( -6x + 32 = 5x \)[/tex]
4. [tex]\( -4x + 16 = 5x \)[/tex]
The equation [tex]\(-6x + 32 = 5x\)[/tex] matches option 3.
Thus, the equivalent equation is:
[tex]\[ \boxed{-6x + 32 = 5x} \][/tex]
1. Start with the original equation:
[tex]\[ 2x - 4(2x - 8) = 5x \][/tex]
2. Simplify the left-hand side by distributing the [tex]\(-4\)[/tex] across the terms within the parentheses:
[tex]\[ 2x - 4(2x - 8) = 2x - 4 \cdot 2x + 4 \cdot 8 \][/tex]
Simplify the multiplication inside:
[tex]\[ 2x - 8x + 32 \][/tex]
3. Combine like terms on the left-hand side:
[tex]\[ 2x - 8x + 32 = -6x + 32 \][/tex]
4. Rewrite the simplified equation:
[tex]\[ -6x + 32 = 5x \][/tex]
At this point, the simplified version of the given equation is [tex]\(-6x + 32 = 5x\)[/tex].
Let's match this to the provided options:
1. [tex]\( -6x - 8 = 5x \)[/tex]
2. [tex]\( -4x + 32 = 5x \)[/tex]
3. [tex]\( -6x + 32 = 5x \)[/tex]
4. [tex]\( -4x + 16 = 5x \)[/tex]
The equation [tex]\(-6x + 32 = 5x\)[/tex] matches option 3.
Thus, the equivalent equation is:
[tex]\[ \boxed{-6x + 32 = 5x} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.